Implementing foreign language curriculum innovation in a Chinese secondary school: An ethnographic study on teacher cognition and classroom practices. (June 2017) - Zhu, Yan; Shu, Dingfang
Abstract: This article reports on a four-year-long ethnographic study on a curriculum innovation project introducing a weak form of communicative language teaching (CLT) at a Chinese secondary school. A total of ten teachers, who taught twelve project classes were observed across five stages of the project: the pre-project stage, the top-down stage, the bottom-up stage; the exam preparation stage, and the post-project stage, in an attempt to explore the changes that took place in the teacher's receptivity and classroom behaviors. Focusing on a focal informant (Marian, pseudonym), this paper illustrates how teacher cognition changed in accordance with the project goal and highlights how the trajectory of change was much more tangled and complicated than what was initially expected. Changes in the project teacher's teaching practices reflect the consistency between teacher cognition and classroom practices at the pre-project, the bottom-up and the post-project stages. In contrast, at the top-down and the exam stages of the innovation project, changes in teachers' cognition did not conform to changes in her classroom practices. These findings suggest the external pressure caused by top-down imperatives and high-stake exams might have caused the cognition-practices incongruence, which deserves language teacher educators' and administrators' further attention when promoting curriculum innovation.